A Potent Auto‐Umpolung Ligand for Conjugative Radical Stabilization. Issue 3 (22nd November 2022) - Holthoff, Jana M.; Engelage, Elric; Ruff, Adrian; Galazzo, Laura; Bordignon, Enrica; Huber, Stefan M.; Weiss, Robert
Abstract: Carbenes with conjugatively connected redox system act as "auto‐umpolung" ligands. Due to their electronic flexibility, they should also be particularly suitable to stabilize open‐shell species. Herein, the first neutral radical of such sort is described in form of a dialkylamino‐substituted bis(dicyanomethylene)cyclopropanide. Despite the absence of steric shielding, the radical is stable for an extended amount of time and was consequently characterized in solution via EPR measurements. These data and accompanying X‐ray structural analyses indicate that the radical species is in equilibrium with aggregates (formed via π‐stacking) and dimers (obtained via σ‐bond formation between methylene carbons). Abstract : A bis(dicyanomethid)cyclopropenium‐based "auto‐umpolung" carbene ligand stabilizes a neutral nitrogen radical. The latter is characterized via EPR measurements in solution and X‐ray structural analyses in the solid state. Both indicate that the radical is in equilibrium with aggregates and a σ‐bound dimer.